No Meaning in the Quran: Sukidi's Thought - Yanuri, Yusuf Rohmat; Setiawan, Ahmad Bayu (QiST: Journal of Quran and Tafseer Studies, 2025)
Where do the meanings lie? This is one of the most intriguing questions in Qur'anic studies both in the West and the East. Some scholars say that the meaning of the Qur'an is inherently located in the scripture. Then, Indonesian Salafism came up with the slogan "Back to the Qur'an". However, some scholars challenged that notion and said that no meaning in the scripture, because meanings are located in the tradition, mufassir. Sukidi Mulyadi proposed the notion of "Back to the tradition", instead of to the Qur'an, because no meaning in the Qur'an. This article will elaborate the Sukidi's notion, elucidate his arguments, examine the context and implications of his claims, and then compare with the views of some related scholars, such as Mun'im Sirry and Sahiron Syamsuddin. This work will use the application of qualitative content analysis. With this approach, this article will provide valuable insights into the complexities of Qur'anic exegesis. By doing so, the study not only clarifies Sukidi's contribution but also highlights the broader intellectual dynamics of meaning-making in Qur'anic exegesis. This article demonstrates the novelty of revisiting Sukidi's thesis in dialogue with contemporary Indonesian scholarship, thereby offering significant insights into the evolving contestations of authority and interpretation in Qur'anic studies.